New trends in software methodologies, tools and techniques : proceedings of the fourth SoMeT W05 - Fujita, Hamido; Mejri, Mohamed, 1968- (Frontiers in artificial intelligence and applications, 2005)
This book presents a number of new trends and theories on the direction in which software science and engineering may develop to transform the role of software and science in tomorrow's information society. This is an attempt to capture the essence of a new state of the art in software science and its supporting technology. It also aims to identify the challenges such a technology has to master. The book comprises papers accepted at the fourth International Conference on New Trends in Software Methodologies, Tools and Techniques, held in Tokyo, Japan in September, 2005.